Design, optimization, and photometric analysis of white light spectrum generated by RGB LEDs using MATLAB - Nguyen, Huynh-Tuan-Anh; Nguyen, Quang-Khoi (Photonics Letters of Poland, 2024)
We have applied MATLAB software to simulate the emission spectra and optimize the parameters in the simulated spectrum to obtain the highest similarity level between simulation and experimental spectra. Also, we have developed algorithms to determine the quantities of the white light spectrum, including correlated color temperature, output lumen, CIE-chromaticity coordinates, tristimulus values, and luminous efficiency of radiation. The optical model and developed photometric calculation algorithm were applied to study the effect of red light on the output white light properties. The result obtained indicates that MATLAB (version R2017b) is a helpful tool in the spectrum design of white light. Full Text: PDF References Schubert, E. (2006). Light-Emitting Diodes (2nd ed.). Cambridge: Cambridge University Press. CrossRef Ching-Cherng Sun et al., "Active thermal-fuse for stopping blue light leakage of white light-emitting diodes driven by constant current", Sci. Rep., 12, 12433 (2022). CrossRef Quang-Khoi Nguyen et al., "First report of emerging fungal pathogens of Cordyceps militaris in Vietnam", Sci. Rep. 13, 13039 (2023). CrossRef G.C. Guarnera, Y. Gitlina, V. Deschaintre, A. Ghosh, "Spectral Upsampling Approaches for RGB Illumination", Euro-graphics Symposium on Rendering (2022). DirectLink C.G. Son, J.H. Yi, J.S. Gwag, J.H. Kwon. "Improvement of Color and Luminance Uniformity of the Edge-Lit Backlight Using the RGB LEDs", J. Opt. Soc. Korea 15, 272 (2011). CrossRef C.-C. Sun, I. Moreno, Y.-C. Lo, B.-C. Chiu, W.-T. Chien, "Collimating lamp with well color mixing of red/green/blue LEDs", Opt. Express, 20, A75 (2012). CrossRef C.-C. Hung, C.-C. Hsieh, Y.-H. Li, C.-C. Lin, "LED Color Mixing Mechanism Design", Appl. Mechanics and Mat. 284-287, 2894 (2013). CrossRef Q.-K. Nguyen, "Emission spectrum modeling of white LEDs light source with using Gaussian function", Photonics Lett. Poland 15(3), 54 (2023). CrossRef H.-T.-A. Nguyen, V.-T. Huynh, Q.-C. Nguyen, Q.-K. Nguyen. "An Optimized method of thermoelectric cooler-based thermal management for improving the luminous efficacy of light-emitting diodes", Photonics Lett. Poland 16(1), 31 (2024) CrossRef C. Li, G. Cui, M. Melgosa, X. Ruan, Y. Zhang, L. Ma, K. Xiao, M.R. Lu, "Accurate method for computing correlated color temperature", Opt. Express, 24, 14066 (2016). CrossRef Commission Internationale de l'Éclairage (CIE), Colorimetry, CIE Publication 15 4th Ed., Draft 11 (personal communication, 2016). DirectLink C.-C. Sun, T.-X. Lee, S.-H. Ma, Y.-L. Lee, S.-M. Huang, "Precise optical modeling for LED lighting verified by cross correlation in the midfield region", Opt. Letters 31, 2193 (2006). CrossRef